For debate: consensus injury definitions in team sports should focus on encompassing all injuries - Hodgson, L.; Gissane, C.; Gabbett, T.; King, D. (Clinical Journal of Sport Medicine, 2007)
Objective: The purpose of this paper is to highlight the most effective method of collecting injury data by using a definition that encompasses all injuries into the data collection system. The definition provides an accurate picture of injury incidence and also allows filtering of records so that data can be reported in a variety of comparable ways.